Rancang Bangun Sistem Informasi Jemaat GPIB Sawangan Bagian Jemaat Ciseeng Berbasis Website - Ebenhaezer Mahardhika Asyer; Sofa Sofiana (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The GPIB Sawangan BAJEM Ciseeng is a place of worship for Christians. Currently, the data processing in this church still does not utilize computer-based information systems. Therefore, the data search process still relies on manual methods such as using Microsoft Word, Microsoft Excel, and physical archives, which takes a long time. Additionally, financial reports can only be viewed once a week during worship, requiring congregation members to come to the church. Furthermore, the church currently disseminates information through printed media, resulting in incomplete and uneven distribution of information. The objective of this research is to analyze and implement a web-based information system to enable the church to organize congregation data efficiently, eliminating the need to search for files individually. The system aims to organize and display data on a website, allowing financial reports to be accessed anywhere and anytime. Moreover, it aims to provide information to a wider range of congregation members in a more uniform manner. The research methodology used in this study is the waterfall model, which consists of requirements analysis, system and software design, implementation and unit testing, system testing, and operation maintenance. The results of this research demonstrate successful organization of congregation data and the creation of financial reports, eliminating the need for congregation members to visit the church to access financial reports. It also ensures comprehensive and uniform distribution of information. The GPIB Sawangan BAJEM Ciseeng website assists the church administrator in managing congregation data, handling financial reports, and providing information on church activities. The author hopes that the GPIB Sawangan BAJEM Ciseeng website can be further developed for Android and iOS platforms.